Engelbert the elephant - Paxton, Tom (New York : Mulberry Books, 1990)
An elephant's dancing skills and good manners surprise everyone at the royal ballm including the queen.
Keywords: Elephants-Fiction; Dancing - Fiction; Stories in rhyme